Tess d Urberville - Thomas Hardy (Open Library, 1891)
A heartbreaking portrayal of a woman faced by an impossible choice in the pursuit of happiness When Tess Durbeyfield is driven by family poverty to claim kinship with the wealthy D'Urbervilles and seek a portion of their family fortune, meeting her 'cousin' Alec proves to be her downfall. A very different man, Angel Clare, seems to offer her love and salvation, but Tess must choose whether to reveal her past or remain silent in the hope of a peaceful future. With its sensitive depiction of the wronged Tess and powerful criticism of social convention, Tess of the D'Urbervilles, subtitled "A Pure Woman," is one of the most moving and poetic of Hardy's novels. Based on the three-volume first edition that shocked readers when first published in 1891, this edition includes as appendices: Hardy's Prefaces, the Landscapes of Tess, episodes originally censored from the Graphic periodical version, and a selection of the Graphic illustrations. For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.
Droits : Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: destin; campagne; Hardy; classique; Littérature